The abundance of benthic dinoflagellates on different substrates - Mohd Hidayat, Nor Salamah; Mohammad Noor, Normawaty; Saad, Shahbudin (IIUM Press, International Islamic University Malaysia, 2017)
Dinoflagellates are second largest of algae in the marine environment after diatom. Many species of dinoflagellates have been identified as harmful algal bloom (HAB) due to the capability of these species to cause a nuisance to the environment and other organism. These dinoflagellates live in many different habitats including in the water column, in sediment and on substrates such as seaweed and seagrass (Mohammad-Noor, 2011). Benthic dinoflagellates preferred mostly the macrophytes as substrates either seaweed or seagrass. A study done in the Gulf of Mexico showed that the highest abundance of Prorocentrum lima can be found on seaweed Ulva fasciata and on seagrass Thalassia testudinum (Okolodkov et al., 2007). Less abundance of dinoflagellates found on dead coral fragments (Millepora alcicornis and Acropora sp.) of the surface of the bottom sediment. Besides, benthic dinoflagellates can also live in sediment. A study done in The Gulf of Taranto reported that there are several species found in sediment which are Ostreopsis ovata, Coolia monotis, Prorocentrum lima and Amphidinium carterae (Caroppo & Bisci,2010). It was also reported that Ostreopsis species are frequently found along the rocky shore where they grow either on macroalgae or directly on the rock or in the sand. In order to study the diversity, distribution, toxicity or ecology of benthic dinoflagellates, sampling method always involved the collection of substrates they are attached. By collecting the natural substrates for example seaweed, the natural ecosystem may be disturbed especially if a lot of substrates need to be collected. Furthermore, substrates preferences among different species of benthic dinoflagellates are also different. Therefore, samples collected may not be standardized and this will lead to unreliable data for comparison among places or habitat. In this study, the suitable of net and petri dish as an artificial substrate were tested. The natural substrates, which are the seaweeds, were collected as a comparison. Besides physical and chemical data was recorded in-situ.